Структура та механічні властивості комбінованих нанокомпозитних покриттів на основі керамічних матеріалів - Мазілін, Богдан Олександрович; Mazilin, B.O. (Харків : ХНУ імені В.Н. Каразіна, 2021)
Mazilin B. O. Structure and mechanical properties of combined nanocomposite coatings on the basis of ceramic materials. – Qualification scholarly paper: a manuscript. Thesis submitted for obtaining the Doctor of Philosophy degree in Natural Sciences, Speciality 105 – Applied physics and nanomaterials. – V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, Kharkiv, 2021. The dissertation work is devoted to solving one of the important problems of modern applied physics and physics of nanomaterials, which is to create a physical and technological basis for the formation of plasma nanocomposite functional coatings based on ceramic compounds and to determine the relationship of structural-phase state of the coatings to the mechanical and physical-chemical properties of the “metal substrate-coating” composites. The aim of this work is to determine the influence of physical and technological deposition parameters on the formation of functional coatings based on multielement ceramic compounds created by ion-plasma evaporation of materials of different composition.
Structure and mechanical properties of combined nanocomposite coatings on the basis of ceramic materials
Дисертаційна робота присвячена вирішенню однієї з важливих задач сучасної прикладної фізики та фізики наноматеріалів, яка полягає у створенні фізико-технологічних основ формування плазмових нанокомпозитних функціональних покриттів на основі керамічних сполук та визначенні зв’язків структурно-фазового стану покриттів з механічними та фізико-хімічними властивостями композитів «металева підкладинка – покриття». Метою роботи є визначення впливу фізико-технологічних параметрів осадження на формування функціональних покриттів на основі керамічних багатоелементних сполук, створених іонно-плазмовим випаровуванням матеріалів різного складу.
Keywords: іонно-плазмові покриття; вакуумно-дугове випаровування; магнетронне розпорошення; нітридні сполуки; багатошарові покриття; нанокомпозити; надтвердий стан; структура; твердість; адгезійна міцність; ion-plasma coatings; vacuum-arc evaporation; magnetron sputtering; nitride compounds; multilayer coatings; nanocomposites; superhard state; structure; hardness; adhesive strength